A Simple and Environmentally Benign Nitration of Pyrazoles by Impregnated Bismuth Nitrate. (9th September 2013) - Ravi, P.; Gore, Girish M.; Tewari, Surya P.; Sikder, Arun K.
<x xml:space="preserve">Abstract</x> We report herein a facile, rapid, and environmentally friendly synthesis of nitropyrazoles in good yields using silica‐bismuth nitrate and silica‐sulfuric acid‐bismuth nitrate at room temperature for the first time. The relatively non‐toxic nature, ease of handling, easy availability, and low cost make the present procedure attractive for the nitration of a wide variety of diazoles in the drug and pharmaceutical industries.